Work Orientations, Well-Being and Job Content of Self-Employed and Employed Professionals. (April 2018) - Warr, Peter; Inceoglu, Ilke
Drawing on psychology-derived theories and methods, a questionnaire survey compared principal kinds of work orientation, job content and mental well-being between self-employed and organisationally employed professional workers. Self-employment was found to be particularly associated with energised well-being in the form of job engagement. The presence in self-employment of greater challenge, such as an enhanced requirement for personal innovation, accounted statistically for self-employed professionals' greater job engagement, and self-employed professionals more strongly valued personal challenge than did professionals employed in an organisation. However, no between-role differences occurred in respect of supportive job features such as having a comfortable workplace. Differences in well-being, job content and work orientations were found primarily in comparison between self-employees and organisational non-managers. The study emphasises the need to distinguish conceptually and empirically between different forms of work orientation, job content and well-being, and points to the value of incorporating psychological thinking in some sociological research.